Menakar Akar Penentu Pembelian Jasa Wisata - Aprih Santoso (Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency Republic of Indonesia, 2021)
This study aims to examine how the effect of service quality on the purchase of tourism services with price perceptions as a moderating variable in the tourist attraction at Goa Kreo Semarang. The population in this study is the visitor society who makes purchases of tourist services at the tourist attraction of Goa Kreo Semarang, where the number is unknown. The sampling method was accident sampling and the sample was 100 people. The results of this study indicate that the variable service quality has a positive and significant effect on the purchase of tourism services at Goa Kreo Semarang. The price perception variable is positively and significantly able to strengthen the relationship between service quality and the purchase of tourist services at Goa Kreo Semarang.